18F-FDG PET/CT in Oral Cuniculatum Carcinoma. (September 2019) - Dejust, Sebastien; El Farsaoui, Khadija; Bellefqih, Sara; Lalire, Paul; Morland, David
Abstract : Abstract: A 69-year-old woman was referred for initial staging of an oral cavity mass. 18 F-FDG PET/CT displayed a homogeneous intense uptake of the 50-mm left hemipalatal mass with local extension to the dental arcade and maxillary sinus. Infracentimetric bilateral cervical nodes with faint uptake were also detected, contrasting with the usual presentation of other head and neck squamous cell carcinoma. Biopsy concluded to a rare head and neck squamous cell carcinoma subtype: oral cuniculatum carcinoma (OCC). After radiotherapy, 18F-FDG PET/CT showed metabolic complete response. Our case describing specifically the metabolic characteristics of OCC and radiotherapy evaluation for this rare tumor.